Sexual dimorphism in hepatic lipids is associated with the evolution of metabolic status in mice. (29th June 2017) - Soares, Ana Francisca; Paz‐Montoya, Jonathan; Lei, Hongxia; Moniatte, Marc; Gruetter, Rolf
Abstract : Ectopic lipid accumulation in the liver is implicated in metabolic disease in an age‐ and sex‐dependent manner. The role of hepatic lipids has been well established within the scope of metabolic insults in mice, but has been insufficiently characterized under standard housing conditions, where age‐related metabolic alterations are known to occur. We studied a total of 10 male and 10 female mice longitudinally. At 3, 7 and 11 months of age, non‐invasive 1 H‐magnetic resonance spectroscopy ( 1 H‐MRS) was used to monitor hepatic lipid content (HLC) and fatty acid composition in vivo, and glucose homeostasis was assessed with glucose and insulin challenges. At the end of the study, hepatic lipids were comprehensively characterized by nuclear magnetic resonance (NMR) and liquid chromatography‐mass spectrometric analyses of liver tissue samples. In males, HLC increased from 1.4 ± 0.1% at 3 months to 2.9 ± 0.3% at 7 months ( p < 0.01) and 2.7 ± 0.3% at 11 months ( p < 0.05), in correlation with fasting insulin levels ( p < 0.01, r = 0.51) and parameters from the insulin tolerance test (ITT; p < 0.001, r = –0.69 versus area under the curve; p < 0.01, r = –0.57 versus blood glucose drop at 1 h post‐ITT; p < 0.01, r = 0.55 versus blood glucose at 3 h post‐ITT). The metabolic performance of females remained the same throughout the study, and HLC was higher than that of males at 3 months (2.7 ± 0.2%, p < 0.01), but comparable at 7 months (2.2 ± 0.2%) and 11 months (2.2 ± 0.1%). Strong sexual dimorphism in bioactive lipid species, including diacylglycerols (higher in males, p < 0.0001), phosphatidylinositols (higher in females, p < 0.001) and omega‐3 polyunsaturated fatty acids (higher in females, p < 0.01), was found to be in good correlation with metabolic scores at 11 months. Therefore, in mice housed under standard conditions, sex‐specific composition of bioactive lipids is associated with metabolic protection in females, whose metabolic performance was independent of hepatic cytosolic lipid content. Abstract : Hepatic cytosolic lipids, as monitored by 1 H‐magnetic resonance spectroscopy ( 1 H‐MRS) in vivo and confirmed by lipidomics of liver triglycerides, do not exhibit major sex‐dependent differences. Insulin sensitivity and hepatic lipid content evolve with age in male, but not female, mice. Sexual dimorphism in bioactive lipids was associated with metabolic scores, probably contributing to the resilience of metabolic health in females for a hepatic lipid load similar to that of males.